Public Perceptions About Mobile Banking at Islamic Banks Duri (Study of Titian Antui Village) - evi lawati; irwandi libra (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2018)
The results of research in the field indicate that the understanding of the community about Islamic bank mobile banking, that is, most people still do not use Islamic bank mobile banking. And people only hear and do not understand using Islamic bank mobile banking. There are still many people in the Titian Antui village who use conventional bank mobile banking because there is only one bank near the Titian Antui village location. The lack of promotion carried out by the thorn sharia bank in the Titian Antui village.